BRICS countries in international investment processes - A. N. Vergun (Vestnik MGIMO-Universiteta)
The article deals with investment activity of BRICS countries as their role in global political and economical processes is growing at a quick rate. The author analyses the main trends of export and import of foreign direct investments, defines geographical and branch directions of investment processes, explores the main forms of inflow and outflow of BRICS investments and highlights investment attractiveness of every country. The author draws special attention to the transnational companies of BRICS countries – the driving force of investment flows.